Competence areas for registered nurses and podiatrists in chronic wound care, and their role in wound care practice - Emilia Kielo; Riitta Suhonen; Leena Salminen; Minna Stolt (WILEY, 2022)
Aims and objectives To identify general competence areas for graduating registered nurses and podiatrists providing chronic wound care. Background The provision of care for chronic wounds involves a team of multiple professionals, and registered nurses and podiatrists play an important role. However, previous studies have found that registered nurses have limited competence in wound care. In addition, there are no standardised international competence areas for the provision of chronic wound care by registered nurses and podiatrists. Design A qualitative design was used in this study. Methods The data were collected using six focus-group interviews with the following professionals: (a) registered nurses; (b) authorised wound care nurses; (c) nurse educators; (d) physicians; (e) podiatrists; and (f) podiatry educators (N = 23). The data were analysed using inductive and deductive content analysis. COREQ guidelines were followed, See Appendix S1. Results The competence areas for registered nurses and podiatrists providing care for chronic wounds include knowledge, skills and performance in anatomy and physiology; aetiology, care and prevention of chronic wounds; and wound management and assessment. The competence areas also include a set of attitudes and values relating to chronic wound care and patients with chronic wounds. Conclusions In nursing and podiatry education and in working life, teaching should focus on these areas of competence in chronic wound care. This would standardise and integrate education on wound care, especially that of chronic wounds. Relevance to clinical practice Wound care is an important part of clinical practice in nursing and podiatry. It is suggested that registered nurses and podiatrists need general competence in chronic wound care to carry out evidence-based, safe, high-quality and cost-effective care. These results could be used to define registered nurses' and podiatrists' competence areas and roles in evidence-based wound care as independent healthcare professionals.